The experiments were carried out to study the influence of different sera on in vitro maturation and early development of ovine embryos. Sera used in this study were FLS (Fetal Lamb Serum), ewe serum collected on Day 0 (ES-DO) and Day 6 (ES-D6) of oestrus cycles. Ovine oocyte were matured and cultured in TCM-199 supplemented with 10 % of different sera. Results of this experiment showed that supplementation of ES-DO or ES-D6 could support maturation rate (Metaphase-II) at 68.7% and 67.6%, respec - Yohan Rusiyanto; Bambang Purwantara; Yuhara Sukra (Media Veteriner, 2000)
The experiments were carried out to study the influence of different sera on in vitro maturation and early development of ovine embryos. Sera used in this study were FLS (Fetal Lamb Serum), ewe serum collected on Day 0 (ES-DO) and Day 6 (ES-D6) of oestrus cycles. Ovine oocyte were matured and cultured in TCM-199 supplemented with 10 % of different sera. Results of this experiment showed that supplementation of ES-DO or ES-D6 could support maturation rate (Metaphase-II) at 68.7% and 67.6%, respectively better than FLS (32.9%). The fertilization rate was significantly higher (p